Cases and materials on international law - Dixon, Martin (Martin J.); McCorquodale, Robert; Williams, Sarah (Oxford University Press, 2016)
A topical and engaging companion for study; placing international law directly in the context of contemporary debate. Dixon, McCorquodale and Williams offer broad coverage of international law, providing an appropriate match for a range of courses and teaching styles.